English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

y =2x^2 -6x + 4
Take the derivative to get the slope.
y' = 4x - 6
Substitute x = 1 into this slope equation.
Therefore, slope = 4(1) - 6 = -2.

2006-10-26 13:21:45 · answer #1 · answered by falzoon 7 · 0 0

y=2x^2 - 6x + 4 where x=1
y = 2(1^2) -(6*1) + 4
y = 2-6+4
y=0
if y=0 and x=1 the slope should be 0 because the line is on the
x-axis.
It's been a while since I've done geometry but I'm pretty sure it's right.

2006-10-26 20:20:38 · answer #2 · answered by nutsnflats 2 · 0 0

y = 2x^2 - 6x + 4
dy/dx = 4x - 6 == mx + b
m = 4

2006-10-26 20:16:08 · answer #3 · answered by Helmut 7 · 0 0

y'=4x-6
y'(1)=-2

2006-10-26 20:14:35 · answer #4 · answered by Greg G 5 · 0 0

fedest.com, questions and answers